PENDIDIKAN KESEHATAN ANAK DI MASA PANDEMI COVID-19 - Dwi Khalisa Putri; Eka Riana (Politeknik 'Aisyiyah Pontianak, 2021)
Background Newborns need good care and attention due to changes in adaptation from intrauterine to extrauterine so that they are still susceptible to exposure to infections caused by viruses and germs during the delivery process and some time after birth. One of the viruses that can infect pregnant women and newborns is Severe Acute Respiratory Syndrome (SARS). COVID-19 has been declared a world pandemic by WHO. WHO provides a definition of health which is perfect both physically, mentally and socially. So that at this time the care of the newborn should be done properly. Some of the mistakes that occur in baby care may be due to the lack of knowledge and education of the parents. The purpose of this community service activity is to improve increasing knowledge about health education the health of newborns during the Covid-19 pandemic. The method of implementing activities is to provide counseling on newborn health education and to conduct knowledge assessments before and after counseling is given. Results, the level of knowledge of mothers before counseling, were that most of them had good knowledge (23.8%), the level of knowledge of mothers after counseling was 76.2%, which were in a good category. Conclusion There is increasing knowledge about health education for newborns during the Covid-19 pandemic.